Short-term feeding of MGA to postpartum cows prior to the breeding season - Gleghorn, J.F.; Marston, T.T.; Wankel, L.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A protocol to make anestrous cows more likely to cycle prior to estrous synchronization would greatly enhance reproductive efficiency. Ease of application, availability, and low cost make feeding melengestrol acetate (MGA) a good choice in such a protocol. MGA, used as a progestin “primer,” has no detrimental effects on cows that are already cycling and reduces the number of cows expressing short cycles.
Keywords: Beef; MGA; Postpartum interval; Pregnancy rate; Short cycle